DEVELOPMENT TENDENCY OF THE GOVERNMENT AND PROSPECTS OF IMPROVEMENT - Madaliev, A.A (International Journal of Psychosocial Rehabilitation, 2020)
The comprehensive development of governance has always been and remains the most pressing issue facing every society. There is an ongoing research on its comprehensive development and is being recognized as an important issue of the day. There are some aspects to further improve governance, to strengthen human factor in ensuring sustainable socio-economic development